2012
DOI: 10.1111/j.1445-5994.2011.02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Implantable cardioverter‐defibrillators: a long‐term view

Abstract: This is the first long-term follow-up study of ICD patients in New Zealand. We observed a low mortality rate when compared with other published registries, but a similar rate of both appropriate and inappropriate shock therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
3
10
0
1
Order By: Relevance
“…7 Also, previous primary prevention observational studies showed similar incidences of appropriate therapy after 5-7 years of follow-up. [11][12][13]20 Appropriate shocks were observed in 24% of the primary prevention patients and 47% of the secondary prevention patients over 12 years, which seems comparable with the 28% appropriate shocks reported by Ronn et al after 6 years in secondary prevention patients. 10 Furthermore, the large ALTITUDE registry reported 33%-38% appropriate shocks after 5 years.…”
Section: Appropriate Device Therapysupporting
confidence: 90%
See 2 more Smart Citations
“…7 Also, previous primary prevention observational studies showed similar incidences of appropriate therapy after 5-7 years of follow-up. [11][12][13]20 Appropriate shocks were observed in 24% of the primary prevention patients and 47% of the secondary prevention patients over 12 years, which seems comparable with the 28% appropriate shocks reported by Ronn et al after 6 years in secondary prevention patients. 10 Furthermore, the large ALTITUDE registry reported 33%-38% appropriate shocks after 5 years.…”
Section: Appropriate Device Therapysupporting
confidence: 90%
“…Other observational studies reported similar mortality rates, although most follow-up periods did not exceed 5 years in these studies. [10][11][12][13][14][15] The incidence of all-cause mortality of ICD recipients was higher in the secondary prevention population; this has not been described before and was only apparent after stratifying for ICD and CRT-D treatments. However, closely reviewing the 3-year mortality rates observed in primary and secondary prevention trials demonstrates a comparable trend.…”
Section: Mortality In Icd and Crt-d Recipientsmentioning
confidence: 82%
See 1 more Smart Citation
“…While this has increased from a proportion of 25% in the 2000-2005 period [14], the greatest proportion of unmet need is in the primary prevention population [4,8]. In the United States 82% of devices implanted are for primary prevention [8], although questions about the suitability of all of these implants have been raised [15].…”
Section: New Icd Implants In 2010 In New Zealand Show Marked Differenmentioning
confidence: 99%
“…For primary prevention in patients with left ventricular ejection fraction (LVEF) below 35%, ICD is now recommended (2). However, only 30% to 50% of implanted patients received appropriate ICD firings, and up to 25% suffered from side effects in the first year after ICD insertion (3,4). In addition, because of steadily growing demand for ICD replacements (5), the financial burden of primary ICD insertion on our healthcare systems is increasing.…”
mentioning
confidence: 99%